A review of effect of welding parameters on the mechanical properties of weld in submerged arc welding process. (2020) - Singh, Aman; Singh, R.P.
Abstract: The proper implementation of any welding process depends upon its input process parameters. The principle aim of this review research paper is to make analysis of various parameters of submerged arc welding process as examined by several researchers for optimum output values. These parameters are welding current, welding speed, welding current, wire diameter, welding voltage and many more. This paper covers a literature review of experiments and theories highlighting the effect of input process parameters on the mechanical properties of weld in submerged arc welding (SAW). This study covers the survey of important literature of several decades. Submerged Arc Welding (SAW) is used as a high metal deposition rate welding process in any fabrication industry. In this process thick metal sheets can be joined efficiently. In this study a clear effect of process parameters on several mechanical properties of weld are reported and concluded.